2018
DOI: 10.1080/13669877.2018.1466825
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the unknown… unknowns: ‘doomsday’ prepping and disaster risk anxiety in the United States

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…Prepping takes place at a range of scales (see Peterson, 1984). Most existing ethnographic research into the practice, such as the work of Huddleston (2016), Mills (2017Mills ( , 2018Mills ( , 2019, and Barker (2019) engaged with respondents who were prepping for 'low-level' events. The focus of this study was on the other end of the scale, whereas Kabel and Chmidling (2014: 258) write, '…modern day preppers build or purchase underground bunkers in which they can safely wait out the impending unrest and resurface at an undetermined point in the future'.…”
Section: B Garrettmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepping takes place at a range of scales (see Peterson, 1984). Most existing ethnographic research into the practice, such as the work of Huddleston (2016), Mills (2017Mills ( , 2018Mills ( , 2019, and Barker (2019) engaged with respondents who were prepping for 'low-level' events. The focus of this study was on the other end of the scale, whereas Kabel and Chmidling (2014: 258) write, '…modern day preppers build or purchase underground bunkers in which they can safely wait out the impending unrest and resurface at an undetermined point in the future'.…”
Section: B Garrettmentioning
confidence: 99%
“…The research undertaken by Mills was larger in scope, spanning eighteen US states and including thirty-nine people. Mills found that partisan politics play a key role in the ideologies undergirding prepping practices and provided grounded evidence regarding prepper's anxieties about the unknown (Mills, 2018(Mills, , 2019. Most recently, Barker's extensive research, which involved in-depth interviews, participant observation of prepper meetups, and online analysis, provocatively suggests that in becoming resilient citizens, preppers are 'recuperating the agency of future temporalities, by finding empowerment, pleasure and vitality in moving closer to their metabolic vulnerability' (Barker, 2019: 11).…”
Section: Prepping As a Social Practicementioning
confidence: 99%
“…America's prepping subculture has -from its post-2008 emergence onwards -been populated by mostly right-wing individuals, each preparing to independently survive major disasters (Mills, 2019). The events these preppers anticipate are generally medium-to-long-term scenarios of serious social collapse, in which food is not available to buy, basic utilities are interrupted, and many people may be dead or dying (Mills, 2018). Today's prepping scene largely supersedes the USA's extreme right-wing 'survivalist' movement, which spanned the mid-1970s, 1980s, and 1990s and was similarly focussed on medium-andlong-term disaster survival (see Mitchell, 2002).…”
Section: Researching Prepping Culturementioning
confidence: 99%
“…Fundamentally, prepping begins with stories about what disasters could, or will, happen in the future (see Mills, 2018). At the same time, while it may appear individualistic and solitary, becoming a 'prepper'…”
Section: Researching Prepping Culturementioning
confidence: 99%
See 1 more Smart Citation